2008
DOI: 10.1080/13854040701218410
|View full text |Cite
|
Sign up to set email alerts
|

Is the Prefrontal Cortex Important For Fluid Intelligence? A Neuropsychological Study Using Matrix Reasoning

Abstract: Patients with prefrontal damage and severe defects in decision making and emotional regulation often have a remarkable absence of intellectual impairment, as measured by conventional IQ tests such as the WAIS/WAIS-R. This enigma might be explained by shortcomings in the tests, which tend to emphasize measures of "crystallized" (e.g., vocabulary, fund of information) more than "fluid" (e.g., novel problem solving) intelligence. The WAIS-III added the Matrix Reasoning subtest to enhance measurement of fluid reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…Previous findings have demonstrated that the behavioral and emotional dysfunction associated with vmPFC damage cannot be explained by impaired cognitive intelligence measured by standard intelligence tests (e.g., WAIS/WAIS-R) (4, 13, 51, 52). Furthermore, although the dlPFC has been associated with cognitive intelligence (53-55), recent lesion evidence failed to support the hypothesis that dlPFC damage would disproportionately impair general measures of cognitive intelligence (e.g., verbal IQ, performance IQ, and full-scale IQ) (51). On the other hand, EI complements cognitive intelligence and permits the evaluation of individual differences in emotional and social processes-such processes are key factors in making the right versus wrong decisions in one's personal life and in influencing our choice about optimal situation-specific social and economic exchange strategies (7,56).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have demonstrated that the behavioral and emotional dysfunction associated with vmPFC damage cannot be explained by impaired cognitive intelligence measured by standard intelligence tests (e.g., WAIS/WAIS-R) (4, 13, 51, 52). Furthermore, although the dlPFC has been associated with cognitive intelligence (53-55), recent lesion evidence failed to support the hypothesis that dlPFC damage would disproportionately impair general measures of cognitive intelligence (e.g., verbal IQ, performance IQ, and full-scale IQ) (51). On the other hand, EI complements cognitive intelligence and permits the evaluation of individual differences in emotional and social processes-such processes are key factors in making the right versus wrong decisions in one's personal life and in influencing our choice about optimal situation-specific social and economic exchange strategies (7,56).…”
Section: Discussionmentioning
confidence: 99%
“…Across three difficult tasks, compared with a control task, only lateral prefrontal cortex (PFC) was activated in all three comparisons. Despite the conceptual elegance of this finding, subsequent studies assessing individual differences in intelligence have implicated a much wider network of regions, using several techniques (Gray and Thompson, 2004), including functional imaging in tandem with mediation analyses (Gray et al, 2003) and the method of correlated vectors (Lee et al, 2006), studies of lesion patients (Tranel et al, 2008), and multivariate molecular genetic measures (Kovas and Plomin, 2006). A critical but unasked question is whether different regions contribute to g as functionally distinct units, each making some unique contribution, or whether the regions are all part of a single functionally unified (but spatially distributed) network.…”
Section: Introductionmentioning
confidence: 99%
“…Verbal IQ in the lower normal range could reflect premorbid level of functioning, precluding strong conclusions. In general, studies exploring the effect of PFC lesions on IQ have yielded mixed results (Anderson, Jacobs, & Harvey, 2005; Tranel, Manzel, & Anderson, 2008). …”
Section: Discussionmentioning
confidence: 99%